The role of total quality management in improving administrative performance among employees at Umm Al-Qura University (The International Journal of Educational Sciences and Arts, 2025)
This study aims to analyze the role of Total Quality Management (TQM) in enhancing administrative performance at Umm Al-Qura University. It examines the core principles of TQM, the challenges associated with its implementation, and the relationship between TQM application and administrative efficiency. The study adopts a descriptive-analytical approach by reviewing previous literature and analyzing the experiences of other universities. The findings indicate that implementing TQM principles positively contributes to improving administrative efficiency, reducing errors, and enhancing employee satisfaction. The study also highlights major challenges, including weak institutional awareness, limited resources, and employee resistance to change. It recommends fostering a culture of quality within the university, developing training programs for employees, improving organizational structures to support TQM implementation, and establishing clear evaluation criteria for continuous performance monitoring.
Keywords: Total Quality Management; Administrative Performance; Universities; Umm Al-Qura University; Quality Improvement